New frontiers for therapeutic endoscopic ultrasound in children - Valerio Balassone; Simona Faraci; Chiara Imondi; Paola De Angelis; Tamara Caldaro; Luigi Dall'Oglio (Society of Gastrointestinal Intervention, 2023)
Therapeutic endoscopic ultrasound is a well-established tool for several gastrointestinal disorders in adults. Diffusion in children is still limited but it can represent an effective, non-invasive option. A selection of relevant clinical cases will be presented.